Nicole Simek. Hunger and Irony in the French Caribbean: Literature, Theory, and Public. New York: Palgrave Macmillan, 2016. - Jennifer Boum Make (Studies in 20th & 21st Century Literature, 2018)
Review of Nicole Simek. Hunger and Irony in the French Caribbean: Literature, Theory, and Public. New York: Palgrave Macmillan, 2016. ix + 201 pp.
Keywords: hunger; irony; French Caribbean